Local alliances in rural urbanization: Land transfer in contemporary China. (July 2020) - Yep, Ray
The relocation of peasants to high-rise buildings is the latest strategy deployed to feed the insatiable hunger for land in China. To free up more land for construction, Chinese peasants are encouraged to abandon their traditional homes and move into newly built high-rise modern apartments. A central feature of this distinctive form of rural urbanization is the transferability of land development rights across the rural–urban divide. Like most policy initiatives in Chinese economic reforms, variations and improvisation in implementation are found across local administrations. Such local disparities carry major implications for rural governance. This article compares and evaluates the experience of local governments in Chongqing and Nantong. Local governments in these two localities face both opportunities and constraints in integrated urban–rural development, a situation which has contributed to contrasting relocation patterns, and consequently variations in intergovernmental relationships at local levels. Enjoying the privilege of experimenting with the 'land bill' (地票) system, local governments in Chongqing have more leeway to stake their claims and are thus in a better position to maintain their authority. In the Nantong case, however, the more hands-on approach of the prefecture deprives lower administrative levels of flexibility to pursue their interests. This contrast in the policy process leads to different patterns of collaboration between levels of government at the grass roots in the two localities, which may also have a long-term impact on the exercise of authority at the community level.